Pengaruh Faktor-Faktor Sosial Terhadap Partisipasi Angkatan Kerja Perempuan Pada Sektor Formal di Indonesia - Mita Permatasari; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study analyzes various social factors that influence women’s participation in the formal labor force in Indonesia. The focus of the research is directed at identifying the variables determining work participation decisions, including education level, marital status, area of ​​residence, job training, and work experience. Using a quantitative method, this study utilizes secondary data from the 2020 National Labor Force Survey (SAKERNAS). The analysis was conducted using a binary logistic regression model with 399,935 female respondents of productive age (15–64 years) to estimate their chances of participation in the formal sector. The findings indicate that education, marital status, place of residence, and job training have a significant positive influence, while work experience is significantly negatively correlated. The Likelihood Ratio test also confirmed that, collectively, all independent variables contribute significantly to women’s participation in the formal sector. Overall, these results underscore that improving access to education and enhancing the efficiency of job training programs are key drivers of women’s engagement in the formal sector. Therefore, this study recommends women’s empowerment policies focused on strengthening human capital through formal education and accredited job training.